Effectiveness of COVID-19 vaccines in people living with HIV in British Columbia and comparisons with a matched HIV-negative cohort: a test-negative design. (February 2023) - Fowokan, Adeleke; Samji, Hasina; Puyat, Joseph H.; Janjua, Naveed Z.; Wilton, James; Wong, Jason; Grennan, Troy; Chambers, Catharine; Kroch, Abigail; Costiniuk, Cecilia T.; Cooper, Curtis L.; Burchell, Ann N.; et al.
Highlights: We estimated the vaccine effectiveness (VE) against SARS-CoV-2 infection in people living with HIV (PLWH). The VE estimates in PLWH were compared with a matched HIV-negative comparator. Two doses of COVID-19 vaccines were effective against SARS-CoV-2 infection among PLWH. However, the VE in PLWH appeared to peak later, and the degree of waning was quicker. ABSTRACT: Objectives: We estimated the effectiveness of COVID-19 vaccines against laboratory-confirmed SARS-CoV-2 infection among people living with HIV (PLWH) and compared the estimates with a matched HIV-negative cohort. Methods: We used the British Columbia COVID-19 Cohort, a population-based data platform, which integrates COVID-19 data on SARS-CoV-2 tests, laboratory-confirmed cases, and immunizations with provincial health services data. The vaccine effectiveness (VE) was estimated with a test-negative design using the multivariable logistic regression. Results: The adjusted VE against SARS-CoV-2 infection was 71.1% (39.7, 86.1%) 7-59 days after two doses, rising to 89.3% (72.2, 95.9%) between 60 and 89 days. VE was preserved 4-6 months after the receipt of two doses, after which noticeable waning was observed (51.3% [4.8, 75.0%]). In the matched HIV-negative cohort (n = 375, 043), VE peaked at 91.4% (90.9, 91.8%) 7-59 days after two doses and was sustained for up to 4 months, after which evidence of waning was observed, dropping to 84.2% (83.4, 85.0%) between 4 and 6 months. Conclusion: The receipt of two COVID-19 vaccine doses was effective against SARS-CoV-2 infection among PLWH pre-Omicron. VE estimates appeared to peak later in PLWH than in the matched HIV-negative cohort and the degree of waning was relatively quicker in PLWH; however, peak estimates were comparable in both populations.